The Economic Impact of Starting, Stopping, and Restarting an Antibiotic Stewardship Program: A 14-Year Experience - John A. Bosso; Isaac F. Mitropoulos; Robert Bergsbaken; Noe Mateo; Craig Harvey; Christopher J. Sullivan; Garry L. Parlier; James Bryan Warren; Mary A. Ullman; John C. Rotschafer (MDPI AG, 2013)
Regions Hospital started a multidisciplinary antibiotic stewardship program (ASP) in 1998. The program effectively shut down from 2002-2004 as key personnel departed and was then restarted but without the dedicated pharmacist and infectious diseases physician. Purchasing data (in dollars or dollars/patient/day) unadjusted for inflation served as a surrogate marker of antibiotic consumption. These data were reviewed monthly, quarterly, and yearly along with antibiotic susceptibility patterns on a semi-annual basis. Segmented regression analysis was use to compare restricted antibiotic purchases for performance periods of 1998-2001 (construction), 2002-2004 (de-construction), and 2005-2011 (reconstruction). After 4 years (1998-2001) of operation, a number of key participants of the ASP departed. For the following three years (2002-2004) the intensity and focus of the program floundered. This trend was averted when the program was revitalized in early 2005. The construction, deconstruction, and reconstruction of our ASP provided a unique opportunity to statistically examine the financial impact of our ASP or lack thereof in the same institution. We demonstrate a significant economic impact during ASP deconstruction and reconstruction.